1991
DOI: 10.1177/088532829100500404
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of 2,4 TDA Formation from Surgitek Polyurethane Foam under Simulated Physiological Conditions

Abstract: Samples of polyurethane foam used in the manufacture of mammary prostheses were enzymatically treated for a total of thirty days. Papain (a plant thiol endopeptidase which has similar activity to the human lysosomal enzyme cathepsin B) was our enzyme of choice since it has both amidase as well as esterase activity. The experiment was conducted under physiological conditions closely simulating the microenvironment likely to be found around an implanted mammary prosthesis. In our tests, 2,4 TDA was formed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In recent studies, polyureas synthesized from MDI, a diamine chain extender, and a PCL530 soft segment have been reported to degrade to non-cytotoxic decomposition products in vivo [28][29][30]. However, other studies have suggested that polyurethanes based on such aromatic polyisocyanates degrade in vivo to carcinogenic and mutagenic compounds [31][32][33]. Therefore, due to the potentially cytotoxic degradation products associated with MDI, we and others have sought to synthesize biodegradable segmented PEUUR elastomers from aliphatic polyisocyanates such as hexamethylene diisocyanate (HDI), BDI and LDI [14,16,18,[34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, polyureas synthesized from MDI, a diamine chain extender, and a PCL530 soft segment have been reported to degrade to non-cytotoxic decomposition products in vivo [28][29][30]. However, other studies have suggested that polyurethanes based on such aromatic polyisocyanates degrade in vivo to carcinogenic and mutagenic compounds [31][32][33]. Therefore, due to the potentially cytotoxic degradation products associated with MDI, we and others have sought to synthesize biodegradable segmented PEUUR elastomers from aliphatic polyisocyanates such as hexamethylene diisocyanate (HDI), BDI and LDI [14,16,18,[34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenic and mutagenic aromatic diamines have been reported as potential degradation products from polyurethanes based upon aromatic diisocyanates; however, the question of whether the concentration of these harmful degradation products attain a physiologically relevant level is currently unresolved and in debate 12, 13. As alternatives to aromatic isocyanates and to eliminate the concern of aromatic amine by‐products, the utilization of diisocyanates based on L ‐lysine14 and other amino acids15 provide a route to synthesizing biodegradable polyurethanes that are expected to yield only nontoxic degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes based on aromatic diisocyanates have also been shown to exhibit less biocompatibility than those synthesized from aliphatic diisocyanates, caused by toxic degradation products. Polyurethanes prepared with toluene diisocyanate have been shown to degrade under physiological conditions to yield 2,4-toluene diamine, which has known toxicity [ 37 ]. Kääriä et al conducted an in vivo study using a polyurethane prepared from the aromatic 4,4′-methylenediphenyl diisocyanate and observed cytotoxicity attributed to the aromatic amine 4,4′-methylenedianiline produced as a degradation product of the polymer [ 38 ].…”
Section: Chemistry Of Polyurethanesmentioning
confidence: 99%